Thiol-Ene Mediated Strategies for Peptide Cyclisation and Bioconjugation - Ostrovitsa, Nikita (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2025)
This thesis presents innovative methodologies for peptide cyclisation, functionalisation, and bioconjugation, providing advanced tools for biomedical research and drug discovery. Central to this work is the application of the radical thiol-ene chemistry, enabling precise on-resin peptide hydrothiolation and versatile chemical modifications. Chapter 2 details the synthesis of vasopressin and somatostatin analogues with tailored ring sizes to study neuropeptide activity. Using a novel on-resin regioselective thiol installation strategy and subsequent disulfide bond formation, high-purity cyclic analogues of vasopressin and somatostatin were produced, offering insights into the effect of the ring size on biological function. Chapter 3 expands the methodology of the on-resin peptide hydrothiolation to native chemical ligation (NCL), streamlining the synthesis of thiolated amino acid analogues at the N-terminus of peptide sequences. This chapter also demonstrates on-resin conjugation of fluorophores, eliminating intermediate purification steps and paving the way for efficient bioconjugation strategies. Chapter 4 introduces a novel approach for late-stage modifications of cyclic peptide by combining chloroacetyl peptide cyclisation with post-cyclisation thiol-ene reactions. An unsaturated vasopressin analogue was utilised as a model peptide to demonstrate compatibility with diverse thiol substrates. Chapter 5 focuses on the development of thiol-containing chemical probes for selective targeting of crotonylation post-translational modifications. Optimised TEC reactions enabled the covalent modification of crotonylated peptides and opened a new avenue for applications in chemoproteomics and protein targeting in complex biological systems.
APPROVED
Keywords: Bioconjugation; Biomolecular Synthesis; Peptide Synthesis; Radical Chemistry